THEORETICAL AND PRACTICAL CONSIDERATIONS ON SOME OF THE DIFFUSION ASPECTS IN THE PRESENCE OF MECHANICAL VIBRATIONS - Maria, Stoicanescu (European Scientific Journal, ESJ, 2014)
This paper presents some considerations regarding the diffusion processes which occur during the sulphocyanurizing of high speed steels in vibratory field. The mechanical vibrations which are introduced into the metallic material contribute to a increase of the thermochemical treatment efficiency due to the elastic deformations of the basic crystalline grid. Therefore, there are obtained harder layers and the treatment duration is significantly shortened.